Primerjalne ali konkurenčne prednosti Ljubljane v procesu evropskih integracij - Pichler-Milanović, Nataša (Urbani izziv, 2001)
The article deals with the comperative advantages of Ljubljana the capital city of Slovenia, in the process of international and European integrations and the competitivness of cities in the framework of the sustainable development paradigm. The aim of the article is to define the advantages and factors that are important for the future role of Ljubljana in the network of European cities, as well as to devise an empirical basisthat can be used for strategist of urban development and researchers in the fields of urban and regional development. Special emphasis is given to the position and role of Ljubljana in comparison to other cities in Slovenia and to the comparitive analysis between Ljubljana and chosen (sample and competative) cities witin the European Union, central European capital cities and nearby cross border cities within the framework of the Alpe-Adria union.
Keywords: European Union; Evropska unija; Ljubljana; mednarodne integracije; mesta; razvojna strategija; sustainable development; trajnostni razvoj; urbani razvoj